Reimagining health services provision for neglected groups: The “personalization from below” phenomenon - Berti Suman, Anna; Heyen, Nils B.; Micheli, Marina (Frontiers in Sociology, 2023)
How can data-driven citizen science activities supporting health research and services provision meet the needs of unrepresented and neglected groups through increased personalization? In this short Perspective, we explore “personalization from below” as a concept designating forms of citizen science-based data altruism that specifically push for and enact a different understanding of both health services and personalization. We develop the argument that such phenomenon taking place outside “institutionalized” health-related practices could make health services provision more inclusive of values that matter to people. We contextualize instances of “personalization from below,” discuss related data governance models and alternative public health interventions, and conclude by outlining three key arguments in favor of “personalization from below” and future research avenues.